Efektivitas Pemakaian Mesin Magic Sugar Cane Terhadap Penurunan Kualitas Nira pada Sistem Tebang Angkut - Rahayu, Retno Muji; Warkoyo, Warkoyo; Harini, Noor; Anggriani, Rista (Jurnal Ilmiah Teknologi Pertanian Agrotechno; Vol 7 No 1 (2022)DO - 10.24843/JITPA.2022.v07.i01.p09, 2022)
Sugarcane plantations have a role in the development of agriculture in Indonesia. Sugarcane plants needed by industry as raw materials for making sugar, which became nine staples. National sugar production has decreased productivity in terms of yield due to the process of delaying milling (down time). Milling delays of up to three days can decrease the quality of sugarcane juice as reviewed from the increase %brix, decreased pH, increase in sugar content reduction %brix and decrease HK. Design the magic machine sugar cane into a sugarcane harvesting machine tool with sugarcane juice output that aims to optimize the quality of sugarcane juice so that there is not fermentation process and inhibit the hydrolysis of sucrose caused by enzymatic reactions and microbiological activity. The method of design starts from the stage of drafting, identification of problems, solution, designing and prototype. The results of the Magic Machine Sugar Cane design are designed with a height of 1.85 meters and a width of 1.65 meters and a length of 3.75 meters consisting of diesel components, cutting blades, cane carriers, cane cutters, wheels, roll mills, filters, handles, frame body and equipped with a storage tube with the principle of maintaining the sugarcane juice temperature to 5 o C. Magic Machine Sugar Cane effective in maintaining the quality of the sugarcane juice during the process of the cutting and transport system.